British factory, Japanese factory : - Dore, Ronald (University of California Press, 1973)
The Japanese way of work is notoriously ‘different’. But is it Japan or Britain which is the odd man out? When originally published this was the first book to explore the real differences, through a point-by-point comparison of two Japanese factories with two British ones making similar products. In the first half of the book this comparison is pursued in systematic detail and clear illustration of the attitudes and assumptions which underlie what the author calls the ‘market-oriented’ system of Britain and the ‘organization-oriented’ system of Japan. One chapter shows how the employment institutions of the two countries fit into their political, family and educational institutions – an exercise in functionalist sociology which dominates t he later chapters and makes a major contribution to the discussion of development and of the ‘convergence’ of different systems.